Pengaruh Telemarketing dalam Kegiatan Business Matching dalam Pameran Indonesia Maritime Expo 2019 - Prita Indah Pertiwi; Djuni Akbar (Bisnis Event, 2020)
The MICE industry (Meetings, Incentives, Conferences, and Exhibitions) is one of the short -term sectors in thetourism industry that is economically important for tourism. Marketing activities are very instrumental inmarketing MICE events. One part of marketing is telemarketing activities. In the B2B exhibition, there aremandatory activities, namely Business Matching. Business Matching is a scheduled business meeting between business people, retailers, agents, distributors and potential investors or partners. The Indonesia Maritime Expo 2019 exhibition is an international-scale business to business (B2B) exhibition. This research is a quantitative study. The sampling method used is the Purprosive Sampling Method. Sampling based on special selection in accordance with the criteria given. The purpose of this research is intended to determine the effect of telemarketing activities as one of the marketing activities at international exhibition events. Telemarketing activities can influence potential buyers in convincing and deciding to do business matching. Telemarketing activities can also provide more detailed information to potential buyers to create new business opportunities with prospective colleagues.